Reflecting on Local Reality: Tensions and Challenges of Sustainable Development in Contexts of Urban Poverty (Glocalism: Journal of Culture, Politics and Innovation, 2018)
The aim of this paper is to present some reflections on the tensions and challenges that emerge from both the literature review on sustainable development and the study of sustainable development as a paradigm in local contexts. In particular, a shantytown located in the outskirts of La Plata city (Argentina) is presented as a case study with the idea that there are some implications between the practices and social representations of people living in urban poverty and the sustainable development paradigm that rules environmental and waste policies in Argentina. The structure of the paper is a combination of two approaches: the macro or top-down approach and the micro or bottom-up approach. The challenge is viewing global as part of local. In addition, two tensions will be introduced: one theoretical at the macro level and one empirical at the micro level. Furthermore, regarding the local context, some preliminary findings of the case study will be introduced.
Keywords: sustainable development; global; local; tensions; urban poverty